PENGELOLAAN ASURANSI HAJI PERSPEKTIF MAQASHID SYARI’AH - Ansori; Ghozali, Muhammad Lathoif; Yasid, Abu (Universitas KH. MUkhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
Establishment of Hajj insurance is a modern solution for Muslims through the DSN-MUI Fatwa Number 39/DSN-MUI/X/2002. The aim is for pilgrims to find peace and protect themselves from disasters and risks during the pilgrimage and the families they leave behind. Hajj insurance uses Tabarru' (grants) and wakalah bil ujrah contracts and sharia insurance institutions acting as grant fund managers are entitled to receive ujrah/rewards for managing these funds in accordance with fair and reasonable principles based on Law No. 34 of 2014 concerning Hajj Financial Management, which is managed by the Hajj Financial Management Agency (BPKH). From the point of view of Maqoshid Al-Syariah, explaining logically and essential in its application so as to give birth to the benefit of the people. The purpose of this study is to analyze the theory of the formation of the DSN-MUI fatwa in establishing legal Istinbath which is related to the formation of haj insurance from the perspective of Maqoshid al-Syari'ah to achieve benefits for the wider community which are dharuriyat in nature including religion, soul, mind, lineage, wealth and honor. . This research method uses descriptive analytical research which aims to develop a theory about a problem, which is associated with certain scientific theories in finding problems rationally. Conclusion The implementation of the Maqashid Ai-Shariah theory provides a clear reference regarding legal sources in the formation of the DSNMUI fatwa regarding haj insurance, so that it can provide maslahah to the wider community. Maqasid al-Syariah's review of hajj insurance is not just theoretical ijtihad but also practical, from the point of view of fiqh law, it becomes a clear reference for legal sources in the formation of DSN MUI fatwa regarding haj insurance.